2002
DOI: 10.2214/ajr.178.6.1781313
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Sensitivity, and Specificity of Individual Signs of Diverticulitis on Thin-Section Helical CT with Colonic Contrast Material: Experience with 312 Cases

Abstract: The two most frequent signs of diverticulitis were bowel wall thickening (96%) and fat stranding (95%). Less frequent but highly specific signs were fascial thickening (50%), free fluid (45%), and inflamed diverticula (43%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 22 publications
3
62
0
13
Order By: Relevance
“…Computed tomography (CT) has emerged as the imaging modality of choice given its high sensitivity and specificity for the diagnosis of diverticulitis, with some studies reporting up to 100% in either measure. [3][4][5][6][7][8] Computed tomography findings of diverticula, inflammation of pericolic fat, bowel wall thickness greater than 4 mm and/or pericolic fluid/abscess are highly suggestive of acute diverticulitis. 1,8,9 A CT scan also provides prognostic information and guides management by determining whether the diverticulitis is complicated by abscess, fistula formation, stricture/obstruction or free rupture.…”
mentioning
confidence: 99%
“…Computed tomography (CT) has emerged as the imaging modality of choice given its high sensitivity and specificity for the diagnosis of diverticulitis, with some studies reporting up to 100% in either measure. [3][4][5][6][7][8] Computed tomography findings of diverticula, inflammation of pericolic fat, bowel wall thickness greater than 4 mm and/or pericolic fluid/abscess are highly suggestive of acute diverticulitis. 1,8,9 A CT scan also provides prognostic information and guides management by determining whether the diverticulitis is complicated by abscess, fistula formation, stricture/obstruction or free rupture.…”
mentioning
confidence: 99%
“…To our knowledge, only two studies in the literature have shown that fecalith may result in diverticulitis and become calcified and visible [6,7]. In our patient, the fecalith became calcified and visible, and we were therefore able to make an appropriate diagnosis.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, when administered orally, the contrast material requires at least two hours to fill the colon [6]. Kircher et al [7] used a rectal contrast material instead of an oral or intravenous contrast material in 312 patients and reported 99% sensitivity and specificity in their study. Thickening of the intestinal mucosa and fat stranding are the most specific symptoms of diverticulitis [8].…”
Section: Discussionmentioning
confidence: 99%
“…This may be associated with the increasing use of CT recently in the emergency radiology. Some studies in the literature also demonstrated that right colonic diverticulitis can be correctly diagnosed using radiologic evaluation [15,16]. Without any further imaging modalities such as CT, right-sided diverticulitis, in particular cecal diverticulitis is quite difficult to distinguish from acute appendicitis before surgery based only on clinical presentations, and the percentage of misdiagnosis is over 90% [17,18].…”
Section: Discussionmentioning
confidence: 99%